2012
DOI: 10.1073/pnas.1213196109
|View full text |Cite
|
Sign up to set email alerts
|

Complex oncogene dependence in microRNA-125a–induced myeloproliferative neoplasms

Abstract: Deregulation of microRNA (miRNA) expression can lead to cancer initiation and progression. However, limited information exists on the function of miRNAs in cancer maintenance. We examined these issues in the case of myeloproliferative diseases and neoplasms (MPN), a collection of hematopoietic neoplasms regarded as preleukemic, thereby representing early neoplastic states. We report here that microRNA-125a (miR-125a)–induced MPN display a complex manner of oncogene dependence. Following a gain-of-function geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 44 publications
4
57
2
Order By: Relevance
“…These observations are in line with data showing an anti-apoptotic effect of miR-125b, especially in the absence of growth factors or low-serum conditions, in several in vitro systems. 24,26,37,38 However, in contrast to others, we find only a limited impact of miR-125b on pre-B-cell proliferation, suggesting that this oncomiR has the dual potential to affect proliferative as well as apoptotic signaling pathways, depending on the priming events or cellular context. 26 The noted discrepancy, however, may be reconciled by the fact that in contrast to primary wild-type B-cell precursors, 1676 cells proliferate already at a high rate that can simply not be enhanced further by miR-125b.…”
Section: Figure 4 Identification Of Target Genes Regulated By Mir-125contrasting
confidence: 45%
“…These observations are in line with data showing an anti-apoptotic effect of miR-125b, especially in the absence of growth factors or low-serum conditions, in several in vitro systems. 24,26,37,38 However, in contrast to others, we find only a limited impact of miR-125b on pre-B-cell proliferation, suggesting that this oncomiR has the dual potential to affect proliferative as well as apoptotic signaling pathways, depending on the priming events or cellular context. 26 The noted discrepancy, however, may be reconciled by the fact that in contrast to primary wild-type B-cell precursors, 1676 cells proliferate already at a high rate that can simply not be enhanced further by miR-125b.…”
Section: Figure 4 Identification Of Target Genes Regulated By Mir-125contrasting
confidence: 45%
“…In support of this notion, it was recently shown that survival of myeloid leukemic cells induced by miR-125a requires continual overexpression of this microRNA and removal of miR125a after cancer development was accompanied by regression of the leukemia. 30 Furthermore, we established that miR-125b functions within both HSPCs and MPs to drive a myeloproliferative disorder in vitro. Indeed, transplanting miR-125b-overexpressing MPs could induce leukemia in recipient mice.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are short, single-stranded RNAs which are associated with gene regulation, at both the transcriptional and translational level, by base-pairing to complementary mRNA sequences in their target genes (17). MiRNAs have diverse functions and are involved in a variety of biochemical processes, including cellular differentiation, proliferation, apoptosis, metabolism and disease, including cancer (18).…”
Section: Discussionmentioning
confidence: 99%